2023
DOI: 10.1038/s41598-023-35907-w
|View full text |Cite
|
Sign up to set email alerts
|

Ebselen derivatives inhibit SARS-CoV-2 replication by inhibition of its essential proteins: PLpro and Mpro proteases, and nsp14 guanine N7-methyltransferase

Abstract: Proteases encoded by SARS-CoV-2 constitute a promising target for new therapies against COVID-19. SARS-CoV-2 main protease (Mpro, 3CLpro) and papain-like protease (PLpro) are responsible for viral polyprotein cleavage—a process crucial for viral survival and replication. Recently it was shown that 2-phenylbenzisoselenazol-3(2H)-one (ebselen), an organoselenium anti-inflammatory small-molecule drug, is a potent, covalent inhibitor of both the proteases and its potency was evaluated in enzymatic and antiviral as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 89 publications
(123 reference statements)
2
14
0
Order By: Relevance
“…Subsequently, it was demonstrated that ebselen also inhibits the papain-like protease (PL pro ) from SARS-CoV-1 and SARS-CoV-2 (with an IC50= 2.26 µM for PL pro of SARS-CoV-2) 11 . The same authors of such pioneering study recently also reported a series of ebselen analogues as potent inhibitors of nsp14 guanine N7-methyltransferase 12 .…”
Section: Introductionmentioning
confidence: 94%
“…Subsequently, it was demonstrated that ebselen also inhibits the papain-like protease (PL pro ) from SARS-CoV-1 and SARS-CoV-2 (with an IC50= 2.26 µM for PL pro of SARS-CoV-2) 11 . The same authors of such pioneering study recently also reported a series of ebselen analogues as potent inhibitors of nsp14 guanine N7-methyltransferase 12 .…”
Section: Introductionmentioning
confidence: 94%
“…Ebselen and its phenyl substituted derivatives have been screened as inhibitors for SARS-CoV-2 M Pro , PL Pro and other non-structural proteins (nsps). 105–110 Biological assays employed to evaluate their anti-SARS-CoV-2 activity in Vero cells revealed that some of these compounds are superior to ebselen as antiviral agents. 110 Like M Pro , the papain-like protease (PL Pro ) of SARS-CoV-2 is also a cysteine protease and is pivotal for viral replication.…”
Section: Organoselenium-based Antiviral Agentsmentioning
confidence: 99%
“…105–110 Biological assays employed to evaluate their anti-SARS-CoV-2 activity in Vero cells revealed that some of these compounds are superior to ebselen as antiviral agents. 110 Like M Pro , the papain-like protease (PL Pro ) of SARS-CoV-2 is also a cysteine protease and is pivotal for viral replication. The IC 50 value for most of the ebselen derivatives against SARS-CoV-2 M Pro inhibition lies in the 1–7.4 μM range.…”
Section: Organoselenium-based Antiviral Agentsmentioning
confidence: 99%
See 2 more Smart Citations